Общетеоретическое решение задачи управления механическими координатами электромеханических систем без измерения токов приводных двигателей - Пересада, Сергей Михайлович; Ковбаса, Сергей Николаевич; Алисов, Андрей Сергеевич (НТУ "ХПИ", 2013)
Control concept for different types of electrical motors with passive electrical part without stator current measurements is presented. Proposed current-sensorless position/speed-flux controller guarantee global asymptotic trajectory tracking in presence of constant unknown load torque. Reported experimental results demonstrate good performances of proposed control scheme, that are suitable for wide applications range. These results can be implemented in the low cost drives with different types of electrical motors.
The general theoretical solution of mechanical coordinates control task for electromechanical systems without stator current measurements
Keywords: электромеханический преобразователь; изменения угловой скорости; изменения углового положения; электрическая подсистема; экспериментальное тестирование; токи приводных двигателей